Trends and Regional Patterns of Cross-Border Mergers and Acquisitions:A Case of Malaysian and Indonesian Acquirers (Journal of International Studies, 2020)
Progress of cross-border mergers and acquisitions (M&A) in Asian region demonstrates an upstream pattern although the economy in Europe is unhealthy. In fact, many cross-border deals in Europe are dominated by Asian and US acquirers. In 2010, Asia Pacific countries had completed over 8,300 M&A deals that involved an Asian company reported by Dealogic. Countries such as China, South Korea, Malaysia, Singapore and Thailand are among Asian countries that are active in cross-border M&A. However, M&A trends in Malaysia and Indonesia have not received due attention of the researchers. Present study attempts to explore this phenomenon with the specific idea of identifying the background of Malaysian and Indonesian industries that involved in cross-border M&A. Present paper also reveals the integration trends involved when engaging in cross-border M&A. An opinion survey was conducted of the firms involved in M&A deals; the companies were identified from the Thomson One Banker main database which covers cross border M&A cases completed in Malaysian and Indonesia. Results show that engineering, software and telecommunication industries are among the leading industries engaged in cross-border M&A. Results also reflect that in terms of nationality of the acquired firms, Malaysia, Indonesia, Thailand and Singapore are among favourites to Malaysian and Indonesian acquirers. The study highlights higher success compared to failures in cross-border M&A in the countries under reference.